Perancangan Pipa Sistem Pemadam Kebakaran di Stasiun Pengumpul Minyak Mentah - Suhaeri; Azhari, Hari (Universitas Pamulang, 2024)
Crude oil gathering stations are locations where crude oil is collected before being transported to processing facilities or ports. The fire suppression system pipeline is an important component in the safety infrastructure of this station. This system is designed to detect, control, and extinguish fires quickly and effectively. In determining the pump must consider the needs of the area to be extinguished. The ring line headers (distribution pipes) or pipes surrounding the crude oil storage area must be designed, and be able to deliver the necessary water needs from the fire pump and pay attention to the economic aspects. The fire assumption designed is if one tank is burned and the other tank is cooled with water to prevent fire. The pump chosen is a centrifugal type pump and in addition a jockey pump is needed to maintain pressure in the main pipe or if the pressure drops to a certain value, the jockey pump will automatically start. The water pool to supply fire protection needs is designed to meet the minimum needs for 4 hours. Based on the design results obtained that the centrifugal pump capacity requirement is 0.148 m3 / s with a power of 25.84 kW and installed 1 pump driven by an electric motor and 1 pump driven by a diesel motor. For the main pipe size, a pipe with a nominal diameter of 12 inches with schedule 40 is needed. For the water pool in the form of roving castings with an effective volume of 4 hours.